A single-ion single-electron cerrous magnet. Issue 42 (12th September 2019) - Gupta, Sandeep K.; Shanmugan, Swaminathan; Rajeshkumar, Thayalan; Borah, Aditya; Damjanović, Marko; Schulze, Michael; Wernsdorfer, Wolfgang; Rajaraman, Gopalan; Murugavel, Ramaswamy
Abstract : A monometallic Ce(iii ) complex derived from bulky phosphonic diamide behaves as a single-ion single-electron magnet. Abstract : Herein, we present monometallic Ln(iii ) complexes [L3 Ln(NO3 )3 ] [where Ln = Ce (1 ) and La (2 )] assembled from a simple reaction of the respective lanthanide nitrate hydrate and a bulky phosphonic diamide t BuPO(NH i Pr)2 ligand (L ), where complex 1 behaves as a single-ion single-electron magnet under a small applied magnetic field. The Ce(iii ) ion occupies a nine-coordinate distorted muffin-like coordination environment. The combination of direct and Raman process dominates the relaxation dynamics in 1 under the applied dc field. The low-temperature measurements performed with oriented crystals on a micro-SQUID setup exhibits strong tunnelling at zero-field, consistent with the theoretical results where strong mixing of the ground state with higher excited m J levels is detected and also throws additional insights on the relaxation dynamics of 1 . Ab initio calculations have been performed to understand the origin of anisotropy and models have been proposed for future directions.